Persaudaraan Orang Muda Katolik: Perbandingan Dokumen Abu Dhabi dan Sinode Keuskupan Bandung 2015 - Leonardus Dewantara, Moses; Viktorahadi, R.F. Bhanu (FOCUS, 2023)
This research explores the role of Catholic Youth (Orang Muda Katolik or OMK) in responding to the challenges of intolerance in Indonesia, particularly in the province of West Java. By examining Catholic Church documents such as the "Abu Dhabi Document" and "Christus Vivit," as well as the Pastoral Focus of the Bandung Diocese for the year 2023, this study aims to understand how OMK comprehends and implements the values of brotherhood advocated by the Church. In the context of intolerance, especially in West Java, known as a region with high levels of intolerance, the research also explores concrete steps that OMK can take to build a more tolerant society. The study involves an analysis of OMK identity, with a focus on the characteristics of the millennial generation, and considers the impact of the document "Human Fraternity for World Peace and Living Together" and the results of the 2015 Synod of the Bandung Diocese. The results indicate that OMK plays a crucial role in fostering interfaith brotherhood, emphasizing dialogue, acceptance of differences, and participation in social action. With implications from Church documents, this research provides a strong foundation for OMK to develop a spirit of brotherhood, respect for differences, and engagement in social action as part of their social responsibility. In the context of pastoral guidance, the study highlights the importance of conscience as a moral guide and suggests pastoral strategies that can be applied to help OMK internalize faith values. Thus, this research provides profound insights into the role of the Catholic Church in promoting peace and brotherhood in the midst of religious intolerance. The results can serve as a basis for further development of strategies to address tolerance challenges at the local and national levels.